2011
DOI: 10.1111/j.1469-0691.2010.03389.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to pneumococcal surface proteins in children with community-acquired pneumonia: a distinct pattern of responses to pneumococcal choline-binding protein A

Abstract: The aetiological diagnosis of community-acquired pneumonia (CAP) is challenging in children, and serological markers would be useful surrogates for epidemiological studies of pneumococcal CAP. We compared the use of anti-pneumolysin (Ply) antibody alone or with four additional pneumococcal surface proteins (PSPs) (pneumococcal histidine triad D (PhtD), pneumococcal histidine triad E (PhtE), LytB, and pneumococcal choline-binding protein A (PcpA)) as serological probes in children hospitalized with CAP. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Second, antibodies to PcpA and PhtD prevent binding of S. pneumoniae to airway epithelium, and here, we observed prevention of binding to primary epithelial cells for the first time. Previous studies have demonstrated a correlation between the levels of antibodies to PcpA (in conjunction with Ply) and reduction in pneumonia (23). Antibodies directed to PcpA and PhtD also appear to correlate with a reduction in bacteremia (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, antibodies to PcpA and PhtD prevent binding of S. pneumoniae to airway epithelium, and here, we observed prevention of binding to primary epithelial cells for the first time. Previous studies have demonstrated a correlation between the levels of antibodies to PcpA (in conjunction with Ply) and reduction in pneumonia (23). Antibodies directed to PcpA and PhtD also appear to correlate with a reduction in bacteremia (11).…”
Section: Discussionmentioning
confidence: 99%
“…PcpA is not required for colonization of the murine nasopharynx (21,22). Human antibodies to PcpA have been detected in infants and children with pneumococcal bacteremia or pneumonia (23). In monovalent vaccines containing PcpA, some level of protection from pneumonia was found, and a delay in morbidity after sepsis challenge was detected in an adult mouse model (21).…”
mentioning
confidence: 95%
“…Other promising proteins that could be used in combination with PspA for a protein vaccine to protect against strains not covered by conjugate vaccines include pneumolysoid, PspC (CbpA), PcpA, and PhtD (9,17,19,22). Regardless of how new vaccines are constructed, it is likely that continued surveillance of pneumococcal serotypes associated with invasive disease will be critical to determine the effectiveness of PCV13 in reducing IPD and to help identify the best vaccine strategy for further improvement in the control of pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies have been conducted, based on reduced sets of proteins showing unclear patterns of antibody response when applied to heterogeneous cohorts of patients (6,13,62). Serological diagnosis of pneumococcal disease is challenging because it should discriminate between infected patients and nonsymptomatic carriers (63), and because of difficulties in obtaining acute and convalescent sera from pediatric patients (1).…”
Section: Figmentioning
confidence: 99%
“…The detection of antibody serological markers by any immunoassay is widely used for early diagnosis, epidemiological surveillance, or evaluation of vaccine immunogenicity against many pathogens, including the pneumococcus (6,12,13). Serological diagnosis of pneumococcal disease based on a single antigen is often challenging, because of the interference of natural antibodies elicited by previous colonization events.…”
mentioning
confidence: 99%